2023
DOI: 10.3389/fphar.2023.1215020
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer therapeutic effect of ginsenosides through mediating reactive oxygen species

Abstract: Dysregulation of reactive oxygen species (ROS) production and ROS-regulated pathways in cancer cells leads to abnormal accumulation of reactive oxygen species, displaying a double-edged role in cancer progression, either supporting transformation/proliferation and stimulating tumorigenesis or inducing cell death. Cancer cells can accommodate reactive oxygen species by regulating them at levels that allow the activation of pro-cancer signaling pathways without inducing cell death via modulation of the antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 194 publications
0
2
0
Order By: Relevance
“…Therefore, prioritizing the development of methods that can effectively prevent, treat, and mitigate toxicity and side effects is imperative. Plant-derived natural active ingredients have demonstrated substantial potential in cancer treatment and prevention [41][42][43], especially those from natural foods. They have gained widespread use as functional and therapeutic foods, proving beneficial in CRC control or as auxiliary anticancer food support [44].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, prioritizing the development of methods that can effectively prevent, treat, and mitigate toxicity and side effects is imperative. Plant-derived natural active ingredients have demonstrated substantial potential in cancer treatment and prevention [41][42][43], especially those from natural foods. They have gained widespread use as functional and therapeutic foods, proving beneficial in CRC control or as auxiliary anticancer food support [44].…”
Section: Discussionmentioning
confidence: 99%
“…Ginseng has excellent pharmacological effects, and its ginsenosides have been reported to have anti-aging effects on skin through enhancing immune function, resisting melanin formation, inhibiting oxidation, and elevating the concentration of collagen and hyaluronic acid [20]. In addition, saponins in ginseng have antioxidant effects and anti-cancer effects and ameliorate intestinal mucosal damage by enhancing HUR and c-Myc levels [21,22]. Others have shown that saponins in ginseng, such as the ginsenoside Rg1, might have the effect of reducing neuronal apoptosis via ERK/CREB/BDNF signaling to improve learning and memory in epileptic rats [23].…”
Section: Introductionmentioning
confidence: 99%